APPLICATION OF PRIMORYE RAW MATERIALS FOR EFFICIENCY COMPOSITE BINDERS - R S Fediuk (RUDN Journal of Engineering Research, 2016)
Studied raw materials of the south of the Far East, can serve as effective components of the cement composite binder. The use of waste products (fly ash thermal power plants, gravel crushing limestone) helps address both economic and environmental objectives. The studies were selected the best raw materials for the further development of the composite binder formulation on the basis of which will be received high performance concrete with high performance.